IRES: incorporated lactococcal bicistronic vector for target gene expression in a eukaryotic system - Abdul Mutalib, Nur Elina; Mat Isa, Nurulfiza; Mohamed Alitheen, Noorjahan Banu; Song, Adelene Ai Lian; Abdul Rahim, Raha (Academic Press, 2014)
Plasmid DNAs isolated from lactic acid bacteria (LAB) such as Lactococcus lactis (L. lactis) has been gaining more interests for its positive prospects in genetic engineering-related applications. In this study, the lactococcal plasmid, pNZ8048 was modified so as to be able to express multiple genes in the eukaryotic system. Therefore, a cassette containing an internal ribosome entry site (IRES) was cloned between VP2 gene of a very virulent infectious bursal disease (vvIBDV) UPM 04190 of Malaysian local isolates and the reporter gene, green fluorescent protein (GFP) into pNZ:CA, a newly constructed derivative of pNZ8048 harboring the cytomegalovirus promoter (Pcmv) and polyadenylation signal. The new bicistronic vector, denoted as pNZ:vig was subjected to in vitro transcription/translation system followed by SDS–PAGE and Western blot analysis to rapidly verify its functionality. Immunoblotting profiles showed the presence of 49 and 29 kDa bands that corresponds to the sizes of the VP2 and GFP proteins respectively. This preliminary result shows that the newly constructed lactococcal bicistronic vector can co-express multiple genes in a eukaryotic system via the IRES element thus suggesting its feasibility to be used for transfection of in vitro cell cultures and vaccine delivery.